Real Time Global Scheduling Analysis for Generalized DAG Task Upon Heterogeneous Machine - Widianjaya, Adhe; Pramadihanto, Dadet; Sukaridhoto, Sritrusta (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
This paper presents a heterogeneous model of real time task system with novel processing rate work parameter. The model considers the precedence constraint with implicit deadline. Global EDF scheduling algorithm was applied on this model and analyzed in the context of its schedulability and capacity augmentation bound. By combining parallel tasks analysis upon identical multiprocessor and their processing rate upon heterogeneous system, we derived utilization augmentation, which is useful for extending capacity augmentation bound. Our experiments showed that there was a schedulable task system which is characterized by utilization augmentation upon heterogeneous system under Global EDF with capacity augmentation bound of (4-m/2)(1+√(U_Aug)). Our model with processing rate is also useful for practical consideration.